2007
DOI: 10.1111/j.1365-2133.2007.08137.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression pattern of interferon-inducible proteins reflects the characteristic histological distribution of infiltrating immune cells in different cutaneous lupus erythematosus subsets

Abstract: Our results demonstrate a close morphological association between the expression pattern of IFN-inducible proteins and the distribution of CXCR3+ CD3+ lymphocytes in all investigated subsets of cutaneous LE. This supports the importance of an IFN-driven inflammation in this condition. Infiltrating lymphocytes carrying CXCL10 in their granules might amplify the lesional inflammation and be responsible for the chronic course of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
120
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 32 publications
12
120
1
1
Order By: Relevance
“…Previous research has shown that sunlight triggers CLE via a CSF-dependent and macrophage-mediated mechanism in mice [40]. The current study (data not shown) and others [41,42] have found that macrophage numbers are elevated in CLE lesions relative to nonlesional skin, but their functional role, if any, in these inflamed sites has not been demonstrated. In this study, macrophage numbers and activation state were not observably altered within skin lesions of patients administered anti-M-CSF, despite 40-50% suppression of CD14 independently of M-CSF.…”
Section: Cd16contrasting
confidence: 57%
“…Previous research has shown that sunlight triggers CLE via a CSF-dependent and macrophage-mediated mechanism in mice [40]. The current study (data not shown) and others [41,42] have found that macrophage numbers are elevated in CLE lesions relative to nonlesional skin, but their functional role, if any, in these inflamed sites has not been demonstrated. In this study, macrophage numbers and activation state were not observably altered within skin lesions of patients administered anti-M-CSF, despite 40-50% suppression of CD14 independently of M-CSF.…”
Section: Cd16contrasting
confidence: 57%
“…A similar PDC component was previously reported by our group in lichen planus (Santoro et al 2005), an inflammatory dermatoses characterized by epithelial cell death. This similarity highlight the potential contribution of J-PDC to the generation epithelial cell death either indirectly (Wenzel et al 2005(Wenzel et al , 2007b or in a more direct fashion via production of effector molecules such as TRAIL (Gilliet et al 2004) and GrB (this study).…”
Section: Discussionmentioning
confidence: 71%
“…Our cohort of 74 patients expands the screened population and establishes PDC infiltration as hallmark of LE cutaneous pathology. PDC content is lower in SLE compared to CLE and this reduction is associated to a global reduction of skin inflammation, suggesting that PDC can drive the cutaneous immigration of other leukocytes via production of Type I IFN (Wenzel et al 2005(Wenzel et al , 2007bWenzel and Tuting 2007) or inflammatory chemokines (Penna et al 2001(Penna et al , 2002b. A potential explanation for the reduction of PDC in SLE can be found in their redistribution to other extra-cutaneous tissues (Fiore et al 2008;Tucci et al 2008) or variability in cutaneous Chemerin expression.…”
Section: Discussionmentioning
confidence: 92%
“…6 Recent studies provide strong evidence for the involvement of innate and cell-mediated immunity, underlining the important role of plasmacytoid dendritic cells, interferon-a and antibody-dependent cell cytotoxicity. [7][8][9] Histologically, the inflammatory infiltrate observed in SCLE lesions consists mainly of activated T cells and macrophages. These inflammatory cells seem to be in close apposition to epidermal basal keratinocytes that undergo apoptosis and cytotoxic injury.…”
Section: Discussionmentioning
confidence: 99%